PENGARUH HARGA DAN KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN GO-JEK DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASIPADA MAHASISWA UNIVERSITAS NEGERI PADANG - Okla Hanifa; Tri Kurniawati; Rose Rahmidani (Universitas Negeri Padang, 2018)
thecompetition intransportation services industry, especially in theonline transportaffect customer satisfaction and loyalty through variable pricing and quality of service. Competition inonline transport makes TBI Go-jek percentage decline. This study was conducted to determine the effect of price and service quality on customer loyalty Go-jek with satisfaction variable as a mediating variable in Padang State University student. Associative type of research is quantitative. Padang State University student who had used the Go-jek is a population in this study with the sampling technique used purposive sampling.The samples used were 100 people. The technique of collecting data using questionnaires and documentation with the Likert scale ratings to measure the respondents' answers. Data were analyzed using path analysis with SPSS version 21.0.The results of this study indicate that partial price and service quality affects customer satisfaction, customer satisfaction further partially significant effect on customer loyalty while price and service quality partially no effect on customer loyalty. Go-jek suggested creating a strategy that can improve customer satisfaction and moving obstacles.Keyword: price and, service quality, customer satisfaction and customer loyalty